HARMFUL ALGAL BLOOMS IN THE MEDITERRANEAN SEA: EFFECTS ON HUMAN HEALTH. (EuroMediterranean Biomedical Journal, 2026)
A harmful algal bloom (HAB) is defined as a bloom that has deleterious effects on plants, animals or humans. Marine algal toxins are responsible for an array of human illnesses as sociated with consumption of seafood or exposure to aerosolized toxins. The effects of algal toxins are generally observed as acute intoxications, whereas the environmental health effects of chronic exposure to low levels of algal toxins are, to date, only poorly documented and an emerging issue. Consumption of seafood contaminated with algal toxins can result in five types of seafood poisoning syndromes: paralytic shellfish poisoning, neurotoxic shellfish poisoning, amnesic shellfish poisoning, diarrhetic shellfish poisoning and ciguatera fish poisoning. The aim of this paper is to provide an overview on HAB-related issues in the Mediterranean Sea.